ChemInform Abstract: Coinage Metal Hydrides: Synthesis, Characterization, and Reactivity. Issue 48 (10th November 2016) - Jordan, Abraham J.; Lalic, Gojko; Sadighi, Joseph P.
Abstract: Review: 262 refs.